Monoclonal antibodies in the treatment of AL amyloidosis: co-targetting the plasma cell clone and amyloid deposits - Popkova, Tereza; Hajek, Roman; Jelinek, Tomas (British journal of haematology, 2020)
Immunoglobulin light-chain amyloidosis (AL amyloidosis) is a rare disease in which a small plasma cell clone produces toxic misfolded proteins that deposit in organs and impair their function. Currently, the only available treatment approach is the elimination of clonal plasma cells. However, a rapid strike that halts and possibly reverses organ damage is crucial. The development of agents that facilitate the clearance of pathological fibrillar deposits, therefore reducing the frailty of patients, is the needed supplement to plasma cell-directed therapy. Monoclonal antibodies provide therapy against malignant plasma cells (daratumumab, isatuximab, elotuzumab) but they are also able to target and eliminate the amyloid from organs (NEOD001, CAEL-101, dezamizumab). From the plasma cell-directed group, daratumumab in monotherapy has proved to be extremely efficient in relapsed AL amyloidosis, exceeding its results in multiple myeloma. Compared to other agents, monoclonal antibodies possess the advantage of high selectivity and low toxicity and could potentially become future game-changers in this field. Co-targetting of the plasma cell clone and amyloid deposits shall together be translated in the revolutionary improved outcome of potentially curable AL amyloidosis.
Keywords: imunologické faktory; lidé; Antibodies, Monoclonal; plazmatické buňky; Immunologic Factors; Plasma Cells; Humans; primární amyloidóza; Plaque, Amyloid; amyloidní plaky; Immunoglobulin Light-chain Amyloidosis; monoklonální protilátky